A brief review of the relationship of executive function assessment and violence. (September 2020) - Burgess, Justin
Abstract: This review analyzes nine studies comparing violent or aggressive groups to nonviolent groups on tests of executive function (EF). The purpose is to determine if those committing violence, or scoring highly on assessments of impulsive aggression, demonstrate significant impairment in EF while controlling for variables such as age, education, head trauma, substance use, and intelligence. The reviewed studies tested a diverse selection of offenders, including murderers, domestic offenders, sexual offenders, perpetrators of assault, and batterers. The characteristic finding from the examined studies was that errors on Trail Making Test- Part B and various scores from the Wisconsin Card Sorting Test differentiated violent and nonviolent persons more consistently than other EF tests used. Violent offenders also performed significantly worse on tests of verbal fluency and general verbal ability compared to nonviolent individuals. Additionally, the Wisconsin Card Sorting Test was able to differentiate between different types of violent offenders. These results held across the type of crime committed, as well as incarcerated individuals, and individuals who self-reported as being physically aggressive. Highlights: Purpose was to determine if those committing violence show impairment in executive function while controlling for variables Participants in studies included murderers, domestic offenders, sexual offenders, perpetuators of assault, and batterers Errors on Trails Making Test- Part B and various scores from Wisconsin Card Sorting Test differentiated violent from non-violent offenders Violent offenders performed worse on verbal fluency and general verbal ability than non-violent offenders Wisconsin Card Sorting Test differentiated between different types of violent offenders